Therapeutic target exploration of Shugan Jianpi formula in liver fibrosis: an integrated lncRNA-mRNA co-expression network analysis - Kaiqiang Wan; Qiong Zhou; Ruirui Feng; Chang Fan; Weibing Shi; Wenbin Xu; Hui Jiang; Qiumei Zhou (Molecular Genetics and Genomics, 2026)

Evaluation and calculation of the 239Pu(n,f) cross section up to 200 MeV - Bo Gao; Changlin Lan; Bo Xie; Kuozhi Xu; Yanliang Chang; Muntazir Mehdi; Fanmin Zeng; Xiaonan Huang; Jianglong Pan; Ruirui Xu; Yue Zhang; Shilong Liu; et al. (Annals of Nuclear Energy, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

The role of silica in biomass for calcium-modified biochar: Phosphorus removal mechanism and potential as a phosphate fertilizer application - Yongyi Chen; Ruiling Zhang; Jiayong Gao; Mujun Han; Songyan Qin; Kai Liu; Yajie Shu; Ruirui Zhang; Chang Shi; Yue Zheng (Journal of Environmental Sciences, 2025)

Centurial sedimentary record of Cd sources and deposition in Chaohu Lake: Insights from Cd stable isotopes - Ruirui Wang; Chuanyu Chang; Wenhan Cheng; Liqiang Xu; Jihua Hao; Fang Huang (Environmental Research, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

Targeting STING oligomerization with licochalcone D ameliorates STING-driven inflammatory diseases - Yinghui Zhang; Yadan Liu; Bing Jiang; Lifan Chen; Jie Hu; Buying Niu; Jie Chang; Zisheng Fan; Jingyi Zhou; Yajie Wang; Dan Teng; Ning Ma; et al. (Science China Life Sciences, 2024)

Quenching-induced amorphisation and configuration transformation for the enhanced electrochemical performance of poly(vinylidene fluoride-hexafluoropropylene)-based solid electrolytes - Yaguang Zhang; Jianxun Zou; Ruirui Chang; Zixuan Min; Shuping Dong; Zhijia Tang; Xuandu Li; Jingjing Tang; Juan Yang; Xiangyang Zhou (Chemical Engineering Journal, 2024)

Historical co-enrichment, source attribution, and risk assessment of critical nutrients and heavy metal/metalloids in lake sediments: insights from Chaohu Lake, China - Chuanyu Chang; Ruirui Wang; Liqiang Xu; Zhenjie Zhao; Wenhan Cheng; Jihua Hao; Fang Huang (Environmental Geochemistry and Health, 2024)

Cadmium accumulation and isotope fractionation in typical protozoa Tetrahymena: A new perspective on remediation of Cd pollution in wastewater - Ruirui Wang; Zhiqiang Zhu; Wenhan Cheng; Chuanyu Chang; Xiaoyuan Song; Fang Huang (Journal of Hazardous Materials, 2023)